Hush, hush - Fitzpatrick, Becca; Simon and Schuster (London : Simon & Schuster BFYR, 2009)
High school sophomore Nora has always been very cautious in her relationships, but when Patch, who has a dark side she can sense, enrolls at her school, she is mysteriously and strongly drawn to him, despite warnings from her best friend, the school counselor, and her own instincts.
Booklist, October 2009.
Horn Book, April 2010.
Library Media Connection, January 2010.
Publisher's Weekly, October 2009.
Young Adult
Keywords: Angels -- Juvenile fiction; Best friends -- Juvenile fiction; Dating (Social customs) -- Juvenile fiction; Friendship -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Supernatural -- Juvenile fiction; Angels -- Fiction; Best friends -- Fiction; Dating (Social customs) -- Fiction; Friendship -- Fiction; High schools -- Fiction; Schools -- Fiction; Supernatural -- Fiction; Occult fiction; School stories